Novel Na+/Ca2+ Exchanger Inhibitor ORM-10962 Supports Coupled Function of Funny-Current and Na+/Ca2+ Exchanger in Pacemaking of Rabbit Sinus Node Tissue - Kohajda, Zsófia; Tóth, Noémi; Szlovák, Jozefina; Loewe, Axel; Bitay, Gergő; Gazdag, Péter; Prorok, János; Jost, Norbert; Levijoki, Jouko; Pollesello, Piero; Papp, Julius Gy.; Varró, András; et al. (Frontiers in Pharmacology, 2020)
Background and purpose: The exact mechanism of spontaneous pacemaking is not fully understood. Recent results suggest tight cooperation between intracellular Ca2+ handling and sarcolemmal ion channels. An important player of this crosstalk is the Na+/Ca2+ exchanger (NCX), however, direct pharmacological evidence was unavailable so far because of the lack of a selective inhibitor. We investigated the role of the NCX current in pacemaking and analysed the functional consequences of the If-NCX coupling by applying the novel selective NCX inhibitor ORM-10962 on sinus node (SAN). Experimental approach: Currents were measured by patch-clamp, Ca2+-transients were monitored by fluorescent optical technique in rabbit SAN cells. Action potentials (AP) were recorded from rabbit SAN tissue preparations. Mechanistic computational data were obtained using the Severi SAN model. Key results: ORM marginally reduced the SAN pacemaking with a marked increase in the diastolic Ca2+ level as well as the transient amplitude. The bradycardic effect of NCX inhibition was augmented when the funny-current (If) was previously inhibited and vice-versa, the effect of If was augmented when the Ca2+ handling was suppressed. Conclusion and implications: We confirmed the contribution of the NCX current in the pacemaker mechanism. Our experimental and modelling data support a close cooperation between If and NCX providing an important functional consequence: as these currents together may establish a strong depolarization capacity providing important safety factor for stable pacemaking. Thus, after individual inhibition of If or NCX, excessive bradycardia or instability cannot be expected because these currents may compensate for the reduction of each other providing safe and rhythmic SAN pacemaking.